Peran Notaris Dalam Kepailitan Dan Penundaan Kewajiban Pembayaran Utang - NURLANI, MEIRINA; Aprita, Serlika; Raspita, Desni; Shalihah, Nawatus (Journal Of Law And Social Society, 2025)
This study discusses the strategic role of notaries in the bankruptcy and Suspension of Debt Payment Obligations (PKPU) process in Indonesia. In practice, notaries not only function as public officials who make and validate authentic deeds, but also play an important role in guaranteeing the validity and evidentiary power of legal documents used in filing bankruptcy and PKPU applications at the Commercial Court. Notaries play a role in the preparation and legalization of various important documents such as debt agreements, financial balance sheets, special powers of attorney, to deeds of transfer of assets and binding of material collateral. In addition, in the curator selection process, notaries have an important function in legalizing administrative documents to ensure the authenticity and integrity of prospective curators. This study uses a normative juridical method with a descriptive-analytical approach, based on positive legal provisions such as Law Number 37 of 2004 concerning Bankruptcy and PKPU and Law Number 2 of 2014 concerning the Position of Notary. The research results show that the existence of an authentic notarial deed provides legal certainty, protection, and legitimacy at every stage of bankruptcy and the PKPU (Deferred Payment for Debt) process, as well as strengthening the integrity of the legal process and protecting the rights of debtors and creditors. Keywords: Notary, Bankruptcy, PKPU, Authentic Deed, Receiver, Legal Certainty